Prototype Design of Remote Monitoring Software of Street Lighting System - Ely Rosely (IJAIT (International Journal of Applied Information Technology), 2017)
Street lightings are used in public area to support people activities throughout the night. Maintenance activities are needed to keep the availability of street lights. The advanced of technologies give ideas to create such tools to support the maintenance. Monitoring and controlling tools are proposed to maintain the availability of street lightings. This paper describes a design of web-based remote monitoring software of street lighting. The street lights should be equipped with GPRS module in transmitting data to the software. This research follows three steps: literature review, analysis, and design. The design tools such as BPMN, use case, ERD, and mockup are used to describe the system. The software can be used to monitor the street lights in the widespread area without having to come to the location.